UJI BEBERAPA TEKNIK GRAFTING MANGGA VARIETAS GADUNG - Astutik Astutik (BUANA SAINS, 2008)
This research aimed to find out the effect on several mangoes grafting techniques on the growth of seed of Gadung mango variety. Five treatments consisting of A = wedge attached [spleed ent], B = inverse wedge attached [plact ent], C = slanting attached [Kina method], D = grafting [budding], and E = double and stems attached [double spled ent] were arranged in a single randomized block design with three replicates. The observed parameters included the beginning of new sprout of bud, the amount buds, height of the bud, the number of leaves, and the width of leaves, as well as the percentage of grafting succeeded. Results showed that several techniques of grafting influenced the initiation of a new fresh bud, bud heights and widths of bud in approximately 8 and 10 week after grafting, number of leaves in each season of observation, and succeed percentage on grafting. Double ent stem attached [double spleep ent] resulted highest quantity with numbers of buds around 2,59, heights of buds around 8,37 cm, number of leaves were about 17,64 ; the width or leaves around wedge attached [100 %] was better than double ent stems attached [92,5 %]